Exploration of the Influence: Self Action, Self Efficacy on Student Creativity in General Biology - Fadhilah Fadhilah (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to explore the relationship between self-action and self-efficacy with students' creativity in Biology practicum activities. In the context of higher education, understanding the factors that influence creativity, such as self-action and self-efficacy, is very important for designing. Methodology: This is a quantitative study with an ex post facto research method. This study involves three variables, two independent variables and one dependent variable. The sample variables were taken using the Simple Random Sampling technique, so that the researcher obtained sample of 74 students. This study used questionnaire instrument. The data analysis techniques used were descriptive statistics and inferential statistics. Main Findings: The results of this study indicate that for self-action and self-efficacy, the average score is in the moderate category. While for student creativity, the average score is also in the moderate category. The results of inferential statistical analysis with the F test indicate a significant influence between self-action and self-efficacy on student creativity in General Biology practicum activities in the Biology Education Study Program, Fatmawati Sukarno State Islamic University, Bengkulu. Novelty/Originality of this study: This research pays attention to psychological aspects, such as how individuals act towards themselves (Self Action) and individual beliefs in their abilities (Self Efficacy), which may have a significant influence on students' ability to produce creativity when participate in General Biology practicum activities. Focusing on the context of practicum activities can illustrate the influence of these variables in real.